الأورو وسياسة سعر الصرف في الدول المغاربية var دراسة حالة الجزائر باستعمال متجه الانحدار الذاتي .2015- للفترة 2000 - souadi, rachda (Finance and Business Economies Review, 2023)
The study aims at identifying the effects of changes in the Euro-Dollar exchange rate on the exchange rate policies in the Maghreb countries, especially as these countries have signed agreements with the EU in the framework of the Euro-Mediterranean Partnership, which increased the terms of trade between them, the study revealed a positive relationship between the euro and the Moroccan dirham and the Tunisian dinar, whereas Algeria faced where the results of the econometric study showed that the effects of fluctuations of the euro is limited because it has a lot of foreign exchange reserves